Answer:
<em>☆</em><em><</em><em> </em><em><u>《</u></em><em><u>HOPE IT WILL HELP YOU</u></em><em>》</em><em>></em><em>☆</em>
Step-by-step explanation:
Y=1.5x+2
<h3>
<em><u>(</u></em><em><u>x</u></em><em><u>=</u></em><em><u>1</u></em><em><u>)</u></em></h3>
y=1.5 (1) +2
y=1.5+2
y=3.5
<h3>
<em><u>(</u></em><em><u>x</u></em><em><u>=</u></em><em><u>2</u></em><em><u>)</u></em></h3>
y=1.5(2)+2
y=3+2
y=5
<h3>
<em><u>(</u></em><em><u>x</u></em><em><u>=</u></em><em><u>3</u></em><em><u>)</u></em></h3>
y=1.5 (3)+2
y=4.5+2
y=6.5
<h3>(x=4)</h3>
y=1.5 (4)+2
y=6+2
y=8
<h3>
<em><u>(</u></em><em><u>x</u></em><em><u>=</u></em><em><u>5</u></em><em><u>)</u></em></h3>
y=1.5 (5)+2
y=7.5+2
y=9.5
<h2>
<em><u>please</u></em><em><u> </u></em><em><u>mark my ans as BRAIN</u></em><em><u> </u></em><em><u>LIST</u></em></h2>
Step-by-step explanation:
2x = y-10
Rewrite as: 2x + 10 = y
Therefore:
2x+10 = y
2x +7 = 2y
Subtract the equations:
2x + 10 = y
- 2x + 7 = 2y
______________
3 = -y
Therefore y = -3
Substiture y = -3 into the second equation:
2x + 7 = 2(-3)
2x + 7 = -6
2x = -13
x= -6.5
Answer : (-6.5, -3)
Is = 2 ………………………………..,…..
Answer:
4/3
Step-by-step explanation:
because 2/3 × 2 = 4/3
brainliest